Anora [videorecording (DVD)] - Baker, Sean, 1971-; Baker, Sean, 1971-; Madison, Mikey; Eydelshteyn, Mark, 2002-; Borisov, I︠U︡riĭ, 1992-; Karagulian, Karren; Tʻovmasyan, Vachʻe, 1986-; Miranda, Luna Sofía, 1999-; Normington, Lindsey, 1996-; Ekamasova, Darʹi︠a︡, 1984-; Serebri︠a︡kov, Alekseĭ, 1964-; Daniels, Drew (Criterion collection, 2025)
Anora, an enterprising, ferociously foulmouthed Brooklyn erotic dancer and sex worker, meets her prince not-so-charming Vanya, a Russian oligarch's wild-child son. After getting assigned to his VIP party because she speaks some Russian, Ani spends a week as his arm candy and the two get married on an impulse. However, she must quickly adjust to the cruel reality of the class divide when his father decides it's time for him to grow up and take his place in the family business, sending his henchmen to annul the marriage and setting off a wild chase through the streets of New York.